In Vitro Digestion Characteristics of Tilapia Myofibrillar Proteins under Different Heating Conditions - Zirui FU; Hui HUANG; Jianwei CEN; Shuxian HAO; Huan XIANG; Shengjun CHEN; Ya WEI; Xiao HU; Chunsheng LI (Shipin gongye ke-ji)
Tilapia was rich in nutrients and serves as an important source of high-quality protein. This study investigated the effects of three thermal processing methods: Steaming at 100 ℃ for 5 minutes, microwaving at 500 W for 5 minutes, and baking at 160 ℃ for 8 minutes, on the quality of tilapia muscle and protein digestibility. The myofibrillar protein content, secondary structure, and protein oxidation indicators were measured following thermal treatment. Additionally, an in vitro digestion simulation was conducted to assess digestibility, degree of hydrolysis, peptide distribution, and amino acid content of tilapia myofibrillar proteins. The results showed that thermal processing induced varying degrees of protein denaturation, characterized by decreased solubility, disruption of hydrogen bonds, significant reduction in α-helix content, and significant increase in β-turn content (P<0.05). Among the groups, the steaming group exhibited significantly lower protein content compared to the baking and microwaving groups (P<0.05). The baking group showed a higher degree of protein oxidation than the steaming and microwaving groups (P<0.05). In vitro digestion experiments revealed that during the gastric digestion phase, the digestibility of the baking and microwaving groups was similar and significantly higher than that of the steaming and raw groups (P<0.05). In the intestinal digestion phase, the degree of hydrolysis for the steaming, baking, and microwaving groups were significantly higher than that of the raw group (P<0.05), with a significant increase in free amino acids and small peptide content. The levels of arginine (Arg) and lysine (Lys) were significantly elevated in the thermally processed groups (P<0.05), which enhancing their antioxidant capacity. In summary, thermal processing not only promoted the digestion of myofibrillar proteins and the release of free amino acids, but also improved the bioactive functions of tilapia digestion products. Mild oxidation in baking group caused minor structural changes and partial unfolding of proteins, which increasing the susceptibility to proteases. So the digestibility of baking group was slightly higher compared to other processing methods.